1993
DOI: 10.1097/00012272-199309000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Palliative fever management in Alzheimer patients

Abstract: Aggressive medical treatment of infections does not affect the progressive course of dementia of the Alzheimer type (DAT) and has limited effect on the mortality rate. Utilization of health care resources and discomfort during a fever episode were compared in three differing treatment conditions: in 18 patients in a dementia special care unit (DSCU) who received palliative management, 26 patients in a DSCU who were treated aggressively, and 17 DAT patients in traditional long-term care units who were treated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Besides these, Dutch reports from leading societies on the acceptability of terminating life in incompetent patients were identified' 7-10 along with the national Dutch Law on the Medical Treatment Agreement (1995). Factors concerning health status and prognosis that could play a role in the decision making process were reported on in numerous studies of community-acquired pneumonia in adult hospitalised patients; these were reviewed in a meta-analysis in 1996 by Fine et al 11 Prognostic information concerning treatment of patients with fever [12][13][14] or lower respiratory tract infections 15 in demented (nursing home) patients was available, but not specifically for pneumonia patients. Specific guidelines for seriously demented patients appeared to be available neither in the Netherlands, nor elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Besides these, Dutch reports from leading societies on the acceptability of terminating life in incompetent patients were identified' 7-10 along with the national Dutch Law on the Medical Treatment Agreement (1995). Factors concerning health status and prognosis that could play a role in the decision making process were reported on in numerous studies of community-acquired pneumonia in adult hospitalised patients; these were reviewed in a meta-analysis in 1996 by Fine et al 11 Prognostic information concerning treatment of patients with fever [12][13][14] or lower respiratory tract infections 15 in demented (nursing home) patients was available, but not specifically for pneumonia patients. Specific guidelines for seriously demented patients appeared to be available neither in the Netherlands, nor elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Studying the various treatments prescribed to relieve symptoms would also be helpful as little is known about their effectiveness. [30][31][32] A potential limitation of our study is selection bias. It is unclear why physicians who participated in both cohorts exhibited less change than physicians who were in only one cohort.…”
Section: Discussionmentioning
confidence: 96%
“…This lack of efficacy of antibiotics in persons with severe dementia may be explained, at least in part, by the fact that infections in this patient population tend to be recurrent and are increasingly caused by resistant organisms [20]. The same authors reported that a significantly higher degree of discomfort occurred during episodes of fever in patients with dementia who had been treated aggressively in standard long-term care units, as compared with those who were looked after in a hospice [21][22][23]. However, the estimated mortality rate for patients with lower severity of dementia was 7 times higher in the hospice approach than it was for those who received antibiotics.…”
Section: Ethical Principlesmentioning
confidence: 99%